ORGANIZATION OF THE BASIC MODEL OF BUSINESS PROCESSES - Uskenbayeva Р.К.; Bolshibayeva А.К.; Rakhmetulayeva С.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article discusses the issues of organizing a general model from local ones. When organizing models into a team, not only the structure of the organization is important, but also the nature of the relationship between the models and the type of protocol (universal or unique), for example, the type of technologies for integrating data, information, knowledge, and rules based on: BUS, AHI, AII, and interfaces, such as a service or agent. But the organization of local models depends on the peculiarities of the local models. Therefore, before considering the organization of local models, we reveal the essence of local models. It is clear, that the properties of a business process of a single monolithic module cannot be fully displayed. Therefore, the concept of a basic model is proposed, which is integrated from the so-called local models. The work reveals the purpose and essence of the functions of local models (LM) and options for organizing the base model (GM) from local models.